Barrett Esophagus: Quality of life and factors associated with illness perception. Issue 7 (6th July 2022) - van der Ende‐van Loon, Mirjam C. M.; Nieuwkerk, Pythia T.; van Stiphout, Stephan H. C.; Scheffer, Robert C. H.; de Ridder, Rogier J. J.; Pouw, Roos E.; Alkhalaf, Alaa; Weusten, Bas L. A. M.; Curvers, Wouter L.; Schoon, Erik J.
Abstract: Background: Health‐related Quality of life (HRQoL) in patients with Barrett's esophagus (BE), a premalignant condition, may be influenced by gastroesophageal reflux disease (GERD) symptoms and the risk of developing esophageal adenocarcinoma. Methods: We aim to investigate HRQoL in non‐dysplastic Barrett Esophagus (NDBE) patients, identify factors associated with a negative illness perception of the diagnosis BE and compare outcomes between patients treated in a specialized BE center with non‐expert centers. In this multi‐center cross‐sectional study, HRQoL of NDBE patients were assessed using the Short Form 36, Hospital Anxiety and Depression Scale, Cancer worry Scale, and Reflux Disease Questionnaire. A multivariable, linear regression analysis was conducted to assess factors associated with illness perception (Illness perception scale) of the BE diagnosis. Outcome parameters of patients from expert centers were compared to non‐expert centers. Results: A total of 859 NDBE patients (mean age 63.6% and 74.5% male), of which 640 from BE expert centers were included. BE patients scored similar or higher means (i.e. better) on generic HRQoL in comparison with a Dutch norm population. The multivariable regression model showed that cancer worry, GERD symptoms, signs of anxiety and depression, and female gender were associated with a negative illness perception of BE. GERD symptoms were reported in the minority (22.4%) of BE patients. Levels of anxiety symptoms were comparable to a Dutch norm population (mean 3.7 vs. 3.9 p 0.183) and lower for depression symptoms (mean 6.8 vs. 7.6 p < 0.001). Overall, there were no differences found on outcomes between expert centers and non‐expert centers. Conclusion: NDBE patients scored similar or better on generic HRQoL, anxiety and depression than an age and gender matched norm population. The presence of cancer worry, gastrointestinal symptoms, anxiety and depression, and female gender are factors associated with a negative illness perception of the diagnosis BE.